Sídlo firmy MEgA - příprava a organizace výstavby - Balčík, Michal (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Předmětem diplomové práce je příprava a organizace výstavby sídla firmy MEgA. Práce se zabývá zařízením staveniště , bezpečnosti a ochraně zdraví při práci, kontrolním a zkušebním plánem, návrhem strojní sestavy, rozpočtem, harmonogramem, rizika při práci a specializaci v rámci vyřízení překopu na komunikaci.

The object of the diploma thesis is a preparing and organization scheme of residence company MEgA. The thesis deals with facilities of a bulding site, safety devices and safety measures at work, control and pilot plans, a design of the machinery, budget and schedule, risk at the work and specialization through earthwork main road.
Residence of company MEgA - preparing and organization scheme
Keywords: Návrh strojní sestavy; dimenze staveništních přípojek; technická zpráva zařízení staveniště; bezpečnost a ochrana zdraví při práci; kontrolní a zkušební plán; rizika při práci a technologický předpis.; Design of the machinery; dimension of building connections; a technical report of facilities of a building site; safety devices and safety measures at work; control and pilot plans; risk at the work and technological rule.